HLA-G5 and G7 Isoforms in Pregnant Women - Saeid Abediankenari; Faramars Farzad; Zahra Rahmani; Mohammad Bagher Hashemi-Soteh (Iranian Journal of Allergy, Asthma and Immunology, 2015)
Human leukocyte antigen-G which is an immune tolerance effecter molecule has an important role in the maintenance of fetus during pregnancy. Abortion is one of the complications of pregnancy period.  In this research, we have studied levels of HLA-G 5, HLA-G7 isoforms in the abortion-threatened pregnant women in comparison with controls. In a case-control study, 101 abortion-threatened women and 101 healthy pregnant women (healthy controls) with age range 21-32 years were studied. Gene expression of HLA-5 and HLA-7 isoforms was analyzed by real-time polymerase chain reaction after mRNA extraction and cDNA synthesis. The results indicated that HLA-G5 was significantly lower in abortion-threatened women in comparison with the control group whereas HLA-G7 was not significantly differentbetween the 2 groups. HLA-G is a vital molecule during pregnancy that can be a key factor in prevention of abortion. It is concluded that determination of HLA-G5 can be of value in pregnancy.